Penatalaksanaan Fisioterapi pada Kasus Ischialgia Sinistra Di RSUD Salatiga - Wijayani, Diah Wahyu; , Yulisna Mutia Sari, SSt.FT., M.Sc () (2016)
Background: Ischialgia is a syndrome (a collection of symptoms) pain in the pelvic nerve ischiadicus tertekannya result. Penjalaran pain up to my feet so weaken the function of the foot either to stand or walk Objective:To know the implementation of the physiotherapy decrease pain, increase muscle strength, the scope of joint motion and functional ability in the case of ischialgia with using modalities Infra red (IR), Transcutaneus electrical neurostimulation (TENS), lumbar traction, and Mc. Kenzieexercises. Results:After therapy for about the obtained result of the assesment of pain in painful T1:5 to T6:2, pain pres T: 6 to T6: 4, motion pain T1:8 to T6:5, increased muscle strength flexi T1:3 to T6:4, extensionT1:3 to T6:4, lateral flexi dx T1:3 to T6:4, lateral flexi sn T1:3 to T6:4, rotation dx T1:3 to T6:4, and rotation sn T1:3 to T6:4, improvement of LGS flexi T1:6cm to T6:10cm, extension T1:3cm to T6:4cm, lateral flexi dx and sn no change and increased functional ability T1:40% to T6:24% . Conclusion: By providing an Infra-red (IR), Transcutaneus electrical neurostimulation (TENS) can reduce pain, lumbar traction can increase the scope of joint motion, exercise Mc Kenzie can increase muscle strength and improve functional ability.